Inequalities in adolescent learning: Does the timing and persistence of food insecurity at home matter?. (June 2019) - Aurino, Elisabetta; Fledderjohann, Jasmine; Vellakkal, Sukumar
Highlights: We investigated adolescent learning disparities by household food insecurity trajectories during childhood in a large emerging economy. "Value-added" models of achievements included early-life cognition and extensive child and household controls. Heterogeneity by timing of occurrence and persistence of food insecurity, and by skill, was present. Chronic household food insecurity and early childhood food security at home followed by later food security were the largest predictors of impaired cognitive skills at 12 years. Food security programmes may have important learning spillovers. Abstract: We investigated inequalities in learning achievements at 12 years by household food insecurity trajectories at ages 5, 8 and 12 years in a longitudinal sample of 1, 911 Indian children. Estimates included extensive child and household controls and lagged cognitive scores to address unobserved individual heterogeneity in ability and early investments. Overall, household food insecurity at any age predicted lower vocabulary, reading, maths and English scores in early adolescence. Adolescents from households that transitioned from food insecurity at age 5 to food security at a later age, and adolescents from chronically food insecure households had the lowest scores across all outcomes. There was heterogeneity in the relationship between temporal occurrence of food insecurity and cognitive skills, based on developmental and curriculum-specific timing of skill formation. Results were robust to additional explanations of the "household food insecurity gap", i.e. education and health investments, parental and children's educational aspirations, and children's psychosocial skills.